SISTEM INFORMASI MANAJEMEN PROYEK PADA PERUSAHAAN KONTRAKTOR - Pramudya, Andihka; Fransen, Lisa Amelia (Jurnal Teknologi Sistem Informasi, 2022)
Contracting company is a type of business field that works in accordance with the contract agreement in the process of planning, working and providing goods and services. The contractor company in this study is one of the companies engaged in the installation of power plant pipes and buildings. In carrying out its operational activities there are still obstacles, so as to facilitate the company, especially managers in making decisions, a Project Management Information System will be developed. This system was developed using the Rational Unified Process (RUP) methodology which consists of inception, elaboration, construction and transition, use case diagrams, class diagrams, activity diagrams, entity relationship diagrams, PHP programming language with Laravel Framework and MySQL database. The results of making this Project Management Information System can help companies, especially managers, in making decisions regarding project scheduling, HR scheduling, determining the use of raw materials and raw material costs and determining labor wages based on detailed project information generated by the Project Management Information System.